Microbial carbon use efficiency and necromass turnover drive persistent carbon formation in paddy soils under straw-returned complex rotation - Yinhang Xia; Jun Chen; Donghai Jiang; Jiao Lin; Yan Xiao; Yongxue Yan; Tingsen Mou; Yeqin Shu; Nader Saad Elsayed; Yumei Chen; Georg Guggenberger; Zhenhua Zhang (Soil and Tillage Research, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Individual and joint association between per- and polyfluoroalkyl substances and skeletal muscle among 6-9 years old children in China - Xue-Mei Liao; Li-Zi Lin; Wan-Ting He; Yun-Ting Zhang; Si-Hui Guo; Shu-Jun Liang; Zhen Hong; Zhe-Qing Zhang; Guang-Hui Dong; Qin-Zhi Wei (International Journal of Hygiene and Environmental Health, 2026)

Enhanced cycling and thermal stability of nickel-rich cathodes for lithium-ion batteries via molecular-weight-tuned polyaniline–polyethylene glycol interphase - Lin-Jie Xie; Jun-Cheng Jiang; Chen Liang; Qing-Song Wang; Hui-Qi Sun; Yan Tang; An-Chi Huang; Fei-Hao Zhu; Chi-Min Shu (Process Safety and Environmental Protection, 2026)

Nanostructured electrospun nitrocellulose: Stabilization mechanisms and degradation kinetics of organic stabilizers - Wen-Jie Xu; Xue-Ning Cheng; Zhong-Xuan Han; Zhan-Jun Yang; Shu-Na Zhao; Hao Liu; Mi Li; Lin Jiang (Fuel, 2026)

Corrigendum to “Effects of vacuum steam pulsed blanching on bioactive compounds, quality attributes, enzyme activities, and microstructural properties of daylily (Hemerocallis citrina Baroni)” [Food Chem. 506 (2026) 148147] - Jun Zhang; Li-Zheng Deng; Wei-Peng Zhang; Ming-Qiang Xu; You-Sheng Shi; Shi-Han Yu; Jing-Shou Zhang; Fan Yang; Shu-Lin Liu; Wei-Qiao Lv; Hong-Wei Xiao (Food Chemistry, 2026)

Identification of the chili powder with illegal additive Sudan I by shifted-excitation Raman difference spectroscopy system - Shu-Wei Hu; Jun-Qin Xu; Yan-Chi Chao; Jhen-Yue Chang; Ding-Zheng Lin (Food Chemistry, 2026)

Mechanisms and control strategies of shrimp melanosis during storage: A review - Duanquan Lin; Qian Hong; Kai-Yuan Cao; Shu-Jun Hong; Yu-Lei Chen; Le-Chang Sun; Min-Jie Cao (Food Bioscience, 2026)

Hybrid photocatalytic–microbial fuel cells systems: Progress, challenges, and forecasts in water-energy-environment nexus - Rabia Tasaduq Hussain; Baala H. Anandapadmanaban; Chi-Wen Lin; Shu-Hui Liu; Jun Haslinda Shariffuddin (Journal of Environmental Chemical Engineering, 2026)

School greenspace and myopia incidence and burden in Chinese children and adolescents: The Guangzhou children and adolescents cohort study - Xiao-Qi Zhu; Yi Sun; Rong Lin; Ya-Na Luo; Jia-Xin Li; Yi-Dan Zhang; Michael S. Bloom; Matthew H.E.M. Browning; Sam SS. Lau; Shu-Jun Fan; Zhi-Qi Li; Ming-Deng Xiang; et al. (Environmental Research, 2026)

Co-solvent-modulated polyamide nanofiltration membranes for high-temperature separation - Wan-Long Li; Xiao-Wei Luo; Wan-Ting Lin; Si-Yuan Zhang; Zi-Lu Zhang; Zi-Jun Zhang; Zhi-Kang Xu; Ling-Shu Wan (Chemical Engineering Journal, 2026)

Multi-stage study of pyrolysis kinetics, combustion characteristics, and fire modeling for selected nature wood species - Yi-Xuan Lin; Qiang Wang; Qi-Xian Li; Qing-Wen Lin; Peng-Rui Man; Shu-Nan Zhou; Yang Li; Jun Deng (Fuel, 2026)

Effects of vacuum steam pulsed blanching on bioactive compounds, quality attributes, enzyme activities, and microstructural properties of daylily (Hemerocallis lilioasphodelus L.) - Jun Zhang; Li-Zheng Deng; Wei-Peng Zhang; Ming-Qiang Xu; You-Sheng Shi; Shi-Han Yu; Jing-Shou Zhang; Fan Yang; Shu-Lin Liu; Wei-Qiao Lv; Hong-Wei Xiao (Food Chemistry, 2026)

A new method to determine the surrounding rock pressure in twin tunnels with small clear spacing - Zhiyu Tian; Chuan He; Guowen Xu; Guojin Lin; YueHeng Shu; Jun Wang; Liang Nie (Tunnelling and Underground Space Technology, 2026)

Systematic assessment and improvement for the intelligent municipal solid waste sorter - Wei-Lung Mao; Shu-Han Huang; Hsu-Cheng Chen; Jun-Wei Zeng; Yu-Hao Lin (Journal of Cleaner Production, 2026)

ER stress disrupts MFN2-related mitophagy via HRD1-PINK1/ parkin axis in bovine embryos - Shu-Ming Shi; Li-Ying Liu; Zhi-Chao Chi; Lin-Yi Qu; Jing-Hang Li; Guan-Lin Jia; Yu-Yan He; Yong-Xun Jin; Ming-Jun Zhang; Xian-Feng Yu (Theriogenology, 2026)

Genome-wide analysis of the sugarcane SUT gene family reveals ShSUT4 as a key regulator of abiotic stress responses - Xue-Ting Zhao; Ahmad Ali; Cui-Lian Feng; Ji-Shan Lin; Rui-Jie Wu; Shu-Zhen Zhang; Guang-Run Yu; Hai-Feng Jia; Yu-Qing Gong; Ting-Ting Zhao; Jun-Gang Wang (Theoretical and Applied Genetics, 2026)

Cradle-to-gate carbon footprint of industrial-scale fermentative production of poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) (PHBH) - Hsien-Tse Chen; Yu-Hsiang He; Pei-Yi Lin; Wei-Shu Huang; Kaarmukhilnilavan R. Srinivasan; Jun-You You; Pei-Yu Sun; Allen H. Hu; Penjit Srinophakun; Maythee Saisriyoot; Si-Yu Li (Journal of Cleaner Production, 2025)

Salidroside improves bovine embryo quality by mitigating oxidative stress and regulating mitochondrial lipid metabolism - Li-Ying Liu; Xian-Feng Yu; Zhi-Chao Chi; Shu-Ming Shi; Tian Lan; Jia-Hui Leng; Jing-hang Li; Yu-Yan He; Lin-Yi Qu; Guan-Lin Jia; Ilkeun Kong; Ming-Jun Zhang; et al. (Theriogenology, 2025)

A novel method for desulfurization of electrolytic manganese residue using KHCO3: Mechanisms of sulfate transformation and heavy metal mineralization - Hongyuan Zhao; Jiancheng Shu; Fan Lin; Jing Wang; Jun Luo; Yong Yang; Mengjun Chen (Process Safety and Environmental Protection, 2025)

Identification of rice taste quality markers using metabolomics techniques - Jun Shu; Weidan Guo; Kangzi Ren; Xiangjin Fu; Zhao Long; Qinlu Lin; Chun Liu; Jiangtao Li (Food Chemistry, 2025)

The proteo- and chitinolytic coordinate mechanisms of Streptomyces sp. SCUT-3 and its application in chitinous wastes recycling - Ming-Shu Zhang; Zhi-Wei Li; Lei Wu; Zi-Yang Luo; Can Qin; Fu-Gen Zhang; Chu-Yan Liang; Hai-Ning Wang; De-Lin Lu; Jun-Jin Deng; Xiao-Chun Luo (Chemical Engineering Journal, 2025)

Synthesis of lithium-ion sieves based on electrolytic manganese anode slime: Characterization and its lithium adsorption performance - Jun Luo; Jiancheng Shu; Hongyuan Zhao; Jing Wang; Shaoqin Chen; Huimin Yang; Fan Lin; Sha Zhang; Mengjun Chen; Yong Yang (Chemical Engineering Journal, 2025)

Microwave-converted insect frass biochar as a high-performance anode for crude glycerol-powered microbial fuel cells - Shu-Hui Liu; Wei-Jun Lai; Chi-Wen Lin; Hui Suan Ng (Journal of Water Process Engineering, 2025)

Genome-wide identification of ApeC domain-containing protein and revealing the function of ChACP-1.10 in oyster mucosal immunity - Tianxiang Lin; Lu Liu; Liang Zeng; Congxin Zhao; Shu Xiao; Haitao Ma; Jun Li; Fan Mao; Yanping Qin; Yuehuan Zhang; Yang Zhang; Zhiming Xiang; et al. (Fish & Shellfish Immunology, 2025)

Microwave-extracted insect melanin as a metal chelator for bimetallic bioelectro-fenton cathodes: A sustainable approach to ibuprofen-contaminated wastewater treatment - Shu-Hui Liu; Hui-Yu Tang; Chi-Wen Lin; Wei-Jun Lai (Chemical Engineering Journal, 2025)

Highly efficient and sustainable bioconversion of cottonseed meal to high-value products through solid-state fermentation by protease-enhanced Streptomyces sp. SCUT-3 - Zhen-Jie Dai; Ming-Shu Zhang; Zhi-Wei Li; De-Lin Lu; Lei Wu; Can Qin; Hai-Ning Wang; Jun-Jin Deng; Xiao-Chun Luo (Chemical Engineering Journal, 2025)

Characteristics and sources of volatile organic compounds and their impacts on ozone formation in a coastal city of southeastern China - Chende Gai; Chuanyou Ying; Xugeng Cheng; Fei Jiang; Jing Lin; Zhixiong Chen; Lei Shu; Jun Hu; Dongsheng Jiang; Mengmiao Yang; Jane Liu (Atmospheric Pollution Research, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

FlashSim: A novel particle-in-cell numerical model for vacuum surface flashover simulation based on finite element method - Hao-Yan Liu; Guang-Yu Sun; Yue-Lin Liu; Shu Zhang; Chang-Chun Qi; Sheng Zhou; Wen-Rui Li; Guan-Jun Zhang (Computer Physics Communications, 2025)

Discovery and configurations assignment of Ile/Leu-containing cyclic peptides with cytotoxic activity, Reniochpeptins A–D, from the marine sponge Reniochalina sp. - Shuai-Shuai Zhang; Zong-Mei Wu; Ying Wu; Ya-Jun Zeng; Yuan-Yuan Zhang; Xin-Li Lin; Si Zhang; Kai-Xuan Zhan; Hou-Wen Lin; Shu-Ping Wang (Phytochemistry, 2025)

Collagenases from hepatopancreas and muscle of Litopenaeus vannamei: Purification, characterization and comparison of their behaviors in collagen degradation - Xu-Chen Xiao; Jia-Yin Huang; Yu-Lei Chen; Kai-Yuan Cao; Ru-Qing Yang; Duan-Quan Lin; Shu-Jun Hong; Yu-Ting Yang; Min-Jie Cao (Food Chemistry, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Single- and combined-heavy metals/metalloids exposures are associated with infertility in US women aged 20–44: NHANES 2013–2020 analysis - He-Bin Chi; Jia-Jia Tang; Xiao-Yuan Fan; Han-Wen Zhang; Feng Tang; Xian-Shu Lin; Bing-Rui Yang; Na Li; Jun Guo; Li-An-Sheng Wu; Qiu-Qi Huang; Yin-Yin Xia (Reproductive Toxicology, 2025)

Unveiling airborne threats: Vertical profiles of multiple emerging pollutants in PM2.5 across the urban atmosphere of Southern China - Shu-Qing Qiu; Yan-Jun Tang; Li-Xin Hu; Cheng-Lei Pei; Da-Chi Hong; Da-Ying Lin; Geng Kang; Sheng-Zhen Zhou; Bao-Ling Liang; She-Jun Chen; Hong Bai; Guang-Guo Ying (Journal of Hazardous Materials, 2025)

Chronic exposure to liquid crystal monomer EBCN at environmentally relevant concentrations induces testicular dysfunction via the gut-testis axis - Jun Wu; Daojun Lv; Wanmei Lin; Yiyou Mao; Yanqing Xia; Leilei Feng; Tianxin Zhao; Xiangming Mao; Fangpeng Shu; Haibin Guo (Journal of Hazardous Materials, 2025)

Selective complex leaching of Cu, Zn, and Cd from recycled copper smelting fly ash using NH3-NH4Cl system and kinetic analysis - Fan Lin; Tianya Lei; Jiancheng Shu; Mengjun Chen; Jibamu Duo; Xiangfei Zeng; Yunhui Han; Shaoqin Chen; Jiaming Chen; Weiping Huang; Jun Luo (Process Safety and Environmental Protection, 2025)

Can biodegradable film replace polyethylene film to obtain similar mulching effects on soil functions and maize productivity in irrigation region? A three-year experimental appraisal - Xiao-Bin Xiong; Peng-Yang Wang; Ze-Ying Zhao; Jing Wang; Shu-Tong Liu; Fu-Jian Mei; Wen-Ying Wang; Yi-Bo Wang; Xiang-Wen Fang; Ying Zhu; Jin-Lin Zhang; Ning Wang; et al. (Journal of Cleaner Production, 2025)

Bioconversion of agriculture by-products with functionally enhanced Streptomyces sp. SCUT-3: Fish skin as a model - Jing-Tao Ni; Ming-Shu Zhang; De-lin Lu; Wen-jun Lu; Lei Wu; Zhen-dong Yang; Can Qin; Zhen-jie Dai; Zhi-wei Li; Wen-jing Feng; Hua-hong Cai; Jia-rui Zhang; et al. (Food Chemistry, 2025)

Identification of a dual functional betulinic acid analog for the treatment of osteoarthritis by phenotypic screening - Ze-Min Lin; Mai Xiang; Wen-Hui Wei; Shu-Hui Fan; Li Chen; Jie Wang; Xiao-Qian Yang; Chun-Hao Yang; Shi-Jun He; Jian-Ping Zuo (Science China Life Sciences, 2025)

Relationship Between Whole Blood Iron Levels and Lipid Profile Parameters in the General Population: Findings from Routine Physical Examination Report - Rou-Jun Pan; Zhi Luo; Yu-Shun You; Jun-Dong Wang; Ya-Qi Chen; Rong-Rong Zhou; Shu-Zi-Qi Chen; Lin-Min Wang; Jun-Xiang Zhao; Hua-Qin Su; Cai-Li Wang; Li-Fen Zhang; et al. (Biological Trace Element Research, 2024)

A zircon petrochronologic perspective on raising the central Tibetan crust - Shu-Hui Ren; Yun-Chuan Zeng; Roberto Weinberg; Ji-Feng Xu; Jian-Lin Chen; Bao-Di Wang; Feng Huang; Xi-Jun Liu; Hong-Xia Yu; Ming-Jian Li (Chemical Geology, 2024)

Wintertime atmospheric forcing of subtropical northeastern Pacific SST variability - Qi Shu; Yu Zhang; Jun-Chao Yang; Shengpeng Wang; Jian Shi; Xudong Wang; Xiaopei Lin (Climate Dynamics, 2024)

The effect of paeoniflorin on the rewarding effect of methamphetamine and the associated cognitive impairment in mice - Xin-shuang Gong; Hai-xing Wang; Xiang-dong Yang; Zhao-ying Yu; Shu-jun Lin; Zhi-ting Zou; Jia-nan Lv; Li-yin Qian; Yu-er Ruan; Zi-zhen Si; Yi Zhou; Yu Liu (Metabolic Brain Disease, 2024)

Positively charged loose nanofiltration membranes via the assembly of amino-quinone networks for efficient dye/salt separation - Tian Gao; Ping Fu; Wan-Long Li; Wan-Ting Lin; Yuan-Hui Yu; Xiao-Jun Huang; Zhi-Kang Xu; Ling-Shu Wan (Desalination, 2024)

Composition modulation of electrocatalysts based on 3d transition metal towards high-performance Zn-air batteries - Ya-Fei Guo; Xu Liu; Shao-Jie Yang; Peng-Fei Wang; Zong-Lin Liu; Jun-Hong Zhang; Chun-Sheng Li; Jie Shu; Ting-Feng Yi (Chemical Engineering Journal, 2024)

A high-entropy strategy for stable structure of sodium ion batteries: From fundamentals to applications - Xu Liu; Xin-Yu Liu; Nan Zhang; Peng-Fei Wang; Zong-Lin Liu; Jun-Hong Zhang; Jie Shu; Yan Sun; Chun-Sheng Li; Ting-Feng Yi (Chemical Engineering Journal, 2024)

Genomic analysis of Alteromonas sp. M12 isolated from the Mariana Trench reveals its role in dimethylsulfoniopropionate cycling - Yue Lin; Min Zhang; Yu-Xiang Lai; Teng Liu; Meng Meng; Yan Sun; Yu Wang; Qing-Yu Dong; Chen-Xi Li; Meng-Xue Yu; Jin Cheng; Shu-Jun Liu; et al. (Marine Genomics, 2024)

Enhancing extracellular monascus pigment production in submerged fermentation with engineered microbial consortia - Song Zhang; Meng Shu; Zihan Gong; Xinyi Liu; Chenyu Zhang; Ying Liang; Qinlu Lin; Bo Zhou; Ting Guo; Jun Liu (Food Microbiology, 2024)

ChRIPK1 caused necroptosis signaling pathway deficiency in Crassostrea hongkongensis - Yucheng Yang; Liang Zeng; Tianxiang Lin; Lu Liu; Congxin Zhao; Shu Xiao; Haitao Ma; Jun Li; Fan Mao; Yanping Qin; Yuehuan Zhang; Yang Zhang; et al. (Fish & Shellfish Immunology, 2024)

Three species of rape responded to cadmium and melatonin alleviating Cd-toxicity in species-specific strategy - Xiao-long Qin; Yu-qing Zhao; De-jun Zhang; Ke-yu Wang; Wen-hui Chen; Zi-Zhong Tang; Yang-er Chen; Shu Yuan; Lin Ye; Ming Yuan (Environmental Pollution, 2024)

Cross-linked g-C3N4 nanofibers enable thermal stable composite membranes for high-performance loose nanofiltration - Wan-Ting Lin; Ping Fu; Wan-Long Li; Yuan-Hui Yu; Zi-Lu Zhang; Hong-Yu Fan; Xiao-Jun Huang; Zhi-Kang Xu; Ling-Shu Wan (Chemical Engineering Journal, 2024)

Positive feedback between the negative phase of interannual component of the Pacific Decadal Oscillation and La Niña - Hong-Shuo Tang; Yu Zhang; Yu Kosaka; Jun-Chao Yang; Qi Shu; Yi Liu; Xiaopei Lin (Climate Dynamics, 2024)

NLRP3 inflammasome activation triggers severe inflammatory liver injury in N, N-dimethylformamide-exposed mice - Xiu-Ning Zhang; Yan-Jing Zhang; Lin Wang; Shu-Jun Hong; Cui-Li Zhang; Xiu-Lan Zhao; Tao Zeng (Science of The Total Environment, 2024)

Polypeptide urea increases rice yield and nitrogen use efficiency through root growth improvement - Shuang Liao; Fei Deng; Wei Zhou; Li Wang; Wu Li; Hui Hu; Shi-lin Pu; Shu-xian Li; Yong Chen; You-feng Tao; Chi Zhang; Qiu-ping Li; et al. (Field Crops Research, 2024)

High resolution osteoclast-targeted imaging-guided osteoporosis alleviation via persistent luminescence nanocomposite - Xiao Lin; Kewen Zhang; Yang Li; Fang Nan; Jun Li; Hui Zhang; Wei Deng; Weihang Ding; Kaixuan Li; Nur Jarhen; Yitong Zhou; Xiao Yu; et al. (Chemical Engineering Journal, 2024)

Sustainable valorizing high-protein feather waste utilization through solid-state fermentation by keratinase-enhanced Streptomyces sp. SCUT-3 using a novel promoter - Wen-Jun Lu; Ming-Shu Zhang; De-Lin Lu; Zhi-Wei Li; Zhen-Dong Yang; Lei Wu; Jing-Tao Ni; Wei-Dong Chen; Jun-Jin Deng; Xiao-Chun Luo (Waste Management, 2024)

Investigation of bacterial diversity from hybrid water sources to multiple terminal sites on an isolated island in the south China sea - Xiao Chen; Xiao-Nan Wu; Jing-Chun Feng; Yi Wang; Shu-Jun Yang; Jie Kong; Ying-Li Zhou; Jun-Lin Hu; Ke Ding; Si Zhang (Journal of Cleaner Production, 2024)

Technological diversity in the tropical-subtropical zone of Southwest China during the terminal Pleistocene: excavations at Fodongdi Cave - Fa-Xiang Huan; Shi-Xia Yang; Feng Gao; Xin-Ying Zhou; Jian-Ping Yue; Yu-Xiu Zhang; Jin-Xu Wu; Qi-Jun Ruan; Kai-Wei Qiu; Jing-wen Xu; Nai-Ru Lin; Yi-Ren Wang; et al. (Archaeological and Anthropological Sciences, 2024)

Overexpression of ABCB transporter genes confer multiple insecticide tolerances in Bactrocera dorsalis (Hendel) (Diptera: Tephritidae) - Lin Wang; Shu-Hang Tian; Wei Zhao; Jin-Jun Wang; Dan-Dan Wei (Pesticide Biochemistry and Physiology, 2023)

The first identification and functional analysis of two drosophila mothers against decapentaplegic protein genes (SpSmad1 and SpSmad2/3) and their involvement in the innate immune response in Scylla paramamosain - Bang-ze Li; Chen-yang Lin; Wen-bin Xu; Yan-mei Zhang; Qing-jun Shao; Wei-ren Dong; Miao-an Shu (Fish & Shellfish Immunology, 2023)

Somatic embryo induction and plantlet regeneration of Canna × generalis from immature zygotic embryo - Zu-yan Gan; Mu-lin Shu; Feng Yang; Guo-fang Wang; Wen-e Zhang; Xue-jun Pan (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

Interaction of derivatives of cellulose and lignin in co-HTC, co-pyrolysis and co-activation - Jingyi Liang; Haisheng Lin; Chao Li; Lijun Zhang; Shu Zhang; Shuang Wang; Jun Xiang; Song Hu; Yi Wang; Xun Hu (Fuel, 2023)

Laccase-triggered one-step fabrication of positively charged phenolic acid-amine networks for nanofiltration - Ping Fu; Di Zhou; Wan-Long Li; Wan-Ting Lin; Xiao-Jun Huang; Zhi-Kang Xu; Ling-Shu Wan (Desalination, 2023)

Progress in biological activities and biosynthesis of edible fungi terpenoids - Hai-Ying Chen; Jin-Yu Lei; Shu-Li Li; Li-Qiong Guo; Jun-Fang Lin; Guang-Hong Wu; Jun Lu; Zhi-Wei Ye (Critical Reviews in Food Science and Nutrition, 2023)

Isopropanol and styrene removal from aqueous solutions and simultaneous power generation using microbial fuel cells with encapsulated deoxygenated anodes - Shu-Hui Liu; Jun-Ru Ke; Hwai Chyuan Ong; Chi-Wen Lin (Journal of Water Process Engineering, 2023)

Degradation of sulfolane-contaminated groundwater in a tubular microbial fuel cell-based electro-Fenton system: Performance, external resistance effects and microbial community - Chi-Wen Lin; Yen-Ni Tsai; Shu-Hui Liu; Ting-Jun Zhu (Journal of Water Process Engineering, 2023)

Enhancement of chromium (VI) removal and power generation by adding biochar to a single-medium sediment-based microbial fuel cell - Chi-Wen Lin; You-Cheng Jhan; Ting-Jun Zhu; Shu-Hui Liu (Journal of Water Process Engineering, 2023)

Kinetics and mechanism study of dyes degradation in electric field-promoting catalytic wet air oxidation process - Lin-Feng Zhai; Yi Hu; Shu-Ya Xu; He-You Guo; Min Sun; Jun Yu; Yan Wang (Journal of Environmental Management, 2023)

Correlation Analysis of Molecularly-Defined Cortical Interneuron Populations with Morpho-Electric Properties in Layer V of Mouse Neocortex - Jun-Wei Cao; Xiao-Yi Mao; Liang Zhu; Zhi-Shuo Zhou; Shao-Na Jiang; Lin-Yun Liu; Shu-Qing Zhang; Yinghui Fu; Wen-Dong Xu; Yong-Chun Yu (Neuroscience Bulletin, 2023)

Microplastics exacerbate co-occurrence and horizontal transfer of antibiotic resistance genes - Xi Yu; Zhen-Chao Zhou; Xin-yi Shuai; Ze-jun Lin; Zhe Liu; Jin-yu Zhou; Yan-han Lin; Guang-shu Zeng; Zi-ye Ge; Hong Chen (Journal of Hazardous Materials, 2023)

5-epi-ent-Kaurane diterpenoids from the aerial parts of Isodon eriocalyx and their anti-atherosclerotic potential - Long Mu; Tian Li; Peng-Lin Wu; Ling-Qiao Cai; Shu-Ying Li; Zi-Yuan Wang; Yuan-Yuan Liu; Jie Wang; Dong Yan; Zheng-Yun Rao; Chao-Jun Wang; Jian Zhang; et al. (Phytochemistry, 2023)

Design of the yielding support used highly deformable elements for a tunnel excavated in squeezing rock - Hong-ming Tian; Yun Tian; Wei-zhong Chen; Xian-jun Tan; Xiao-yun Shu; Xia-lin Liu (Journal of Mountain Science, 2023)

Sensitivity and reusability of a simple microbial fuel cell-based sensor for detecting bisphenol A in wastewater - Ting-Jun Zhu; Chi-Wen Lin; Shu-Hui Liu (Chemosphere, 2023)

Optimizing the parameters of microbial fuel cells using response surface methodology to increase Cr(VI) removal efficiency and power production - Chi-Wen Lin; Yi-Pei Chung; Shu-Hui Liu; Wei Tong Chen; Ting-Jun Zhu (Process Safety and Environmental Protection, 2023)

Genome-wide identification, structural and evolutionary characteristics, and expression analysis of aquaporin gene family members in Mercenaria mercenaria - Cong Zhou; Zhi-shu Lin; Ying Shi; Jie Feng; Zhi Hu; Mei-jie Yang; Pu Shi; Yong-ren Li; Yong-jun Guo; Tao Zhang; Hao Song (Frontiers in Marine Science, 2023)
Aquaporins (AQPs) are highly-selective transmembrane water transporters that are involved in the adaptation to environmental challenges. However, the structure, function, and evolution of AQPs in bivalves remain largely unknown. In this study, AQP gene family members were identified in nine bivalve species, and their abundance rangs from 7 to 15. Nine AQPs (MmAQPs) were identified in the genome of hard clam ( Mercenaria mercenaria ), which is a euryhaline bivalve that has evolved sophisticated osmoregulatory mechanisms and salinity adaptation. Structurally, all MmAQPs contain 6 or 12 transmembrane α-helices, a major intrinsic protein (MIP) domain, and 2 asparagine-proline-alanine (NPA) motifs. MmAQPs were classified into three subfamilies based on phylogenetic analysis: AQP1-like, AQP3-like, and AQP8-like. No AQP11-like subfamily member was identified in the genome of hard clam. Tandem duplication resulted in a lineage-specific expansion in AQP8-like subfamily in hard clams. MmAQP8 genes showed different expression sensitivity to different environmental stressors. The gene expression patterns of three MmAQP8 were similar under heat, hypoxia, and air exposure stress, but differed greatly under salinity stress, indicating that tandem duplication events may accelerate the functional divergence of AQP8 genes in hard clams. AQP3-like members may have undergone gene loss during evolution, resulting in weakened glycerol and urea penetration in hard clams. Three orthologs of MmAQPs were detected in the genomes of Cyclina sinensis and Archivesica marissinica through synteny analyses. Tissue expression profiles showed that MmAQP genes were highly expressed in the foot and hepatopancreas. Under environmental stress, the expression levels of most of the MmAQP genes changed significantly to maintain metabolic homeostasis. Several MmAQP genes were downregulated to reduce water permeability under salinity and air exposure stress. Several MmAQP genes were significantly upregulated to promote the transmembrane transport of ammonia and reactive oxygen species and activate anti-apoptotic responses to resist stress. This study provides a comprehensive understanding of the AQP gene family in hard clams, and lays a foundation for further studies to explore the functions of AQPs in bivalves.

Enhanced sulfolane-contaminated groundwater degradation and power generation by a mini tubular microbial fuel cell/electro-Fenton combined system - Shu-Hui Liu; Yen-Ni Tsai; Chiaying Chen; Chi-Wen Lin; Ting-Jun Zhu (Process Safety and Environmental Protection, 2023)

Promoting removal of copper from sediment and production of bioelectricity by sediment microbial fuel cells using tea extracts - Shu-Hui Liu; Chu-Yuan Yang; Chi-Wen Lin; Ting-Jun Zhu (Journal of Water Process Engineering, 2023)

Highly efficient shrimp shell recovery by solid-state fermentation with Streptomyces sp. SCUT-3 - De-Lin Lu; Ming-Shu Zhang; Jun-Jin Deng; Wen-Jun Lu; Zhen-Dong Yang; Zhi-Wei Li; Yu-Chen Chen; Xiao-Chun Luo (Chemical Engineering Journal, 2023)

Structure, Intracellular Localisation and Expression Analysis of Sucrose Nonfermenting-Related Kinase ShSnRK1α in Sugarcane - Ting-ting Zhao; Jun-gang Wang; Wen-zhi Wang; Cui-lian Feng; Xiao-yan Feng; Lin-bo Shen; Shu-zhen Zhang (Sugar Tech, 2023)

DNA methylation reprogramming provides insights into light-induced anthocyanin biosynthesis in red pear - Hai-Nan Liu; Qun Shu; Kui Lin-Wang; Richard V. Espley; Andrew C. Allan; Mao-Song Pei; Xiao-Long Li; Jun Su; Jun Wu (Plant Science, 2023)

Control measure implications of COVID-19 infection in healthcare facilities reconsidered from human physiological and engineering aspects - Ying-Fei Yang; Yi-Jun Lin; Shu-Han You; Tien-Hsuan Lu; Chi-Yun Chen; Wei-Min Wang; Chung-Min Liao (Environmental Science and Pollution Research, 2022)

Geomechanics model test and numerical simulation of 2G-NPR bolt support effect in an active fault tunnel - Shu-lin Ren; Man-chao He; Wei-jun Lin; Teng-wu Zhang; Zhi-gang Tao (Journal of Mountain Science, 2022)

Assessing the effect of probiotics on tilapia lake virus‐infected tilapia: Transmission and immune response - Ying‐Fei Yang; Jidapa Yamkasem; Win Surachetpong; Yi‐Jun Lin; Shu‐Han You; Tien‐Hsuan Lu; Chi‐Yun Chen; Wei‐Min Wang; Chung‐Min Liao (Journal of Fish Diseases, 2022)
Probiotics have been used to alleviate disease transmission in aquaculture. However, there are limited studies on probiotic use in modulating tilapia lake virus (TiLV). We assessed commercially available probiotic supplements used in TiLV‐infected tilapia and performed mortality and cohabitation assays. We developed a mechanistic approach to predict dose–response interactions of probiotic effects on mortality and immune gene response. We used a susceptible–infected–mortality disease model to assess key epidemiological parameters such as transmission rate and basic reproduction number ( R 0 ) based on our viral load dynamic data. We found that the most marked benefits of probiotics are significantly associated with immune system enhancements (~30%) and reductions in disease transmission (~80%) and R 0 (~70%) in tilapia populations, resulting in a higher tolerance of farming densities (~400 fold) in aquaculture. These findings provide early insights as to how probiotic use‐related factors may influence TiLV transmission and the immune responses in TiLV‐infected tilapia. Our study facilitates understanding the mode of action of probiotics in disease containment and predicting better probiotic dosages in diet and supplements to achieve the optimal culturing conditions. Overall, our analysis assures that further study of rationally designed and targeted probiotics, or mechanistic modelling is warranted on the basis of promising early data of this approach.

Characteristics and changes of the Himalayas glacial area in China during 1990–2015 - Shu-xian Shi; Li Xing; Yue-kai Ding; Jun Dong; Rui Liu; Qin Ji; Zuo-lin Xiao; Xun Huang (Journal of Mountain Science, 2022)

Deformation characteristics and thresholds of the Tanjiawan landslide in the Three Gorges Reservoir Area, China - Fu-ling Zhang; Mao-lin Deng; Qing-lin Yi; Shu-qiang Lu; Wei-jun Zheng; Hai-feng Huang; Xing Zhu (Journal of Mountain Science, 2022)

Geographical and interspecific variation in susceptibility of three common thrips species to the insecticide, spinetoram - Yong-Fu Gao; Ya-Jun Gong; Li-Jun Cao; Jin-Cui Chen; Yu-Lin Gao; Majid Mirab-balou; Min Chen; Ary A. Hoffmann; Shu-Jun Wei (Journal of Pest Science, 2021)

Multiplex RT–PCR Assay for the Simultaneous Detection and Identification of Five Sugarcane Viruses - Xiao-Yan Feng; Wen-Zhi Wang; Lin-Bo Shen; Jun-Gang Wang; Guo-Ru Xiong; Cui-Lian Feng; Ting-Ting Zhao; Shu-Zhen Zhang (Sugar Tech, 2020)

Targeted selective degradation of Bruton’s tyrosine kinase by PROTACs - Shaodong Liu; Yang Da; Feng Wang; Renjie Yan; Yongzhi Shu; Pei Lin; Jun Lin (Medicinal Chemistry Research, 2020)

Assessing dietary exposure risk to neonicotinoid residues among preschool children in regions of Taiwan - Min-Pei Ling; Huai-An Hsiao; Szu-Chieh Chen; Wei-Yu Chen; Wei-Chun Chou; Yi-Jun Lin; Shu-Han You; Ying-Fei Yang; Hsing-Chieh Lin; Chi-Yun Chen; Tien-Hsuan Lu; Chung-Min Liao (Environmental Science and Pollution Research, 2020)

Novel B-chromosome-specific transcriptionally active sequences are present throughout the maize B chromosome - Zi-Jie Hong; Jun-Xiang Xiao; Shu-Fen Peng; Yao-Pin Lin; Ya-Ming Cheng (Molecular Genetics and Genomics, 2020)

Design, synthesis, and biological evaluation of small molecule PROTACs for potential anticancer effects - Yang Da; Shaodong Liu; Pei Lin; Feng Wang; Renjie Yan; Yongzhi Shu; Jun Lin (Medicinal Chemistry Research, 2020)

Erratum to: Exosome-derived galectin-9 may be a novel predictor of rejection and prognosis after liver transplantation - Ai-bin Zhang; Yi-fan Peng; Jun-jun Jia; Yu Nie; Shi-yu Zhang; Hai-yang Xie; Lin Zhou; Shu-sen Zheng (Journal of Zhejiang University-SCIENCE B, 2020)

Characteristics, Expression Pattern and Intracellular Localisation of Sugarcane Cytoplasmic Hexokinase Gene ShHXK8 - Jun-gang Wang; Ting-ting Zhao; Ben-peng Yang; Wen-zhi Wang; Cui-lian Feng; Xiao-yan Feng; Lin-bo Shen; Shu-zhen Zhang (Sugar Tech, 2019)

Two-factor ANOVA of SSH and RNA-seq analysis reveal development-associated Pi-starvation genes in oilseed rape - Zhong-Wei Zhang; Ling-Yang Feng; Jian-Hui Wang; Yu-Fan Fu; Xin Cai; Chang-Quan Wang; Jun-Bo Du; Ming Yuan; Yang-Er Chen; Pei-Zhou Xu; Ting Lan; Guang-Deng Chen; et al. (Planta, 2019)

Reverse Transcription–Recombinase Polymerase Amplification Assay for the Detection of Sugarcane Streak Mosaic Virus in Sugarcane - Xiao-Yan Feng; Lin-Bo Shen; Wen-Zhi Wang; Jun-Gang Wang; Zheng-Ying Cao; Shu-Zhen Zhang (Sugar Tech, 2019)

Exosome-derived galectin-9 may be a novel predictor of rejection and prognosis after liver transplantation - Ai-bin Zhang; Yi-fan Peng; Jun-jun Jia; Yu Nie; Shi-yu Zhang; Hai-yang Xie; Lin Zhou; Shu-sen Zheng (Journal of Zhejiang University-SCIENCE B, 2019)

Slope deformation monitoring in the Jiufenershan landslide using time domain reflectometry technology - Shei-Chen Ho; I-Hui Chen; Yu-Shu Lin; Jun-Yang Chen; Miau-Bin Su (Landslides, 2019)

Development of a Reverse Transcription-Recombinase Polymerase Amplification Assay for Detection of Sugarcane Yellow Leaf Virus - Xiao-Yan Feng; Lin-Bo Shen; Wen-Zhi Wang; Jun-Gang Wang; Zheng-Ying Cao; Cui-Lian Feng; Ting-Ting Zhao; Shu-Zhen Zhang (Sugar Tech, 2018)

Response to “Letter to the editor re: Cheng YH, Chou WC, Yang YF, et al. Environ Sci Pollut Res (2018). https://doi.org/10.107/s11356-017-0875-4” - Yi-Hsien Cheng; Wei-Chun Chou; Ying-Fei Yang; Chi-Wei Huang; Chun Ming How; Szu-Chieh Chen; Wei-Yu Chen; Nan-Hung Hsieh; Yi-Jun Lin; Shu-Han You; Chung-Min Liao (Environmental Science and Pollution Research, 2018)

Preference and performance of the two-spotted spider mite Tetranychus urticae (Acari: Tetranychidae) on strawberry cultivars - Ya-Jun Gong; Jin-Cui Chen; Liang Zhu; Li-Jun Cao; Gui-Hua Jin; Ary A. Hoffmann; Chuan-Fei Zhong; Peng Wang; George Lin; Shu-Jun Wei (Experimental and Applied Acarology, 2018)

Spatial patterns in natural Picea crassifolia forests of northwestern China, as basis for close-to-nature forestry - Zhi-bin He; Shu Fang; Long-fei Chen; Jun Du; Xi Zhu; Peng-fei Lin (Journal of Mountain Science, 2018)

Enhanced catalytic activities and modified substrate preferences for taxoid 10β-O-acetyl transferase mutants by engineering catalytic histidine residues - Lin-Feng You; Jia-Jun Huang; Tao Wei; Shu-Ling Lin; Bing-Hua Jiang; Li-Qiong Guo; Jun-Fang Lin (Biotechnology Letters, 2018)

MiR-26a functions as a tumor suppressor in ambient particulate matter-bound metal-triggered lung cancer cell metastasis by targeting LIN28B–IL6–STAT3 axis - Yan-Yang Lu; Yi Lin; Dong-Xiao Ding; Shu Su; Qiao-Qiao Chi; You-Chi Zhang; Jian Sun; Xu Zhang; Hui-Min Zhu; Qian-Sheng Huang; Yu-Lang Chi; Guo-Zhu Ye; et al. (Archives of Toxicology, 2018)

Correlation analyses revealed global microRNA–mRNA expression associations in human peripheral blood mononuclear cells - Lan Wang; Jiang Zhu; Fei-Yan Deng; Long-Fei Wu; Xing-Bo Mo; Xiao-Wei Zhu; Wei Xia; Fang-Fei Xie; Pei He; Peng-Fei Bing; Ying-Hua Qiu; Xiang Lin; et al. (Molecular Genetics and Genomics, 2018)

PBPK/PD assessment for Parkinson’s disease risk posed by airborne pesticide paraquat exposure - Yi-Hsien Cheng; Wei-Chun Chou; Ying-Fei Yang; Chi-Wei Huang; Chun Ming How; Szu-Chieh Chen; Wei-Yu Chen; Nan-Hung Hsieh; Yi-Jun Lin; Shu-Han You; Chung-Min Liao (Environmental Science and Pollution Research, 2018)

Mixture risk assessment due to ingestion of arsenic, copper, and zinc from milkfish farmed in contaminated coastal areas - Yi-Jun Lin; Min-Pei Ling; Szu-Chieh Chen; Wei-Yu Chen; Nan-Hung Hsieh; Yi-Hsien Cheng; Shu-Han You; Wei-Chun Chou; Ming-Chao Lin; Chung-Min Liao (Environmental Science and Pollution Research, 2017)

First complete genome sequence of parainfluenza virus 5 isolated from lesser panda - Jun-Qiong Zhai; Shao-Lun Zhai; Tao Lin; Jian-Kui Liu; He-Xing Wang; Bing Li; He Zhang; Shu-Zhan Zou; Xia Zhou; Meng-Fan Wu; Wu Chen; Man-Lin Luo (Archives of Virology, 2017)

Integrative multi-omics analysis revealed SNP-lncRNA-mRNA (SLM) networks in human peripheral blood mononuclear cells - Wei Xia; Xiao-Wei Zhu; Xin-Bo Mo; Long-Fei Wu; Jian Wu; Yu-Fan Guo; Ke-Qin Zeng; Ming-Jun Wang; Xiang Lin; Ying-Hua Qiu; Lan Wang; Pei He; et al. (Human Genetics, 2017)

Assessing exposure risks for freshwater tilapia species posed by mercury and methylmercury - Yi-Hsien Cheng; Yi-Jun Lin; Shu-Han You; Ying-Fei Yang; Chun Ming How; Yi-Ting Tseng; Wei-Yu Chen; Chung-Min Liao (Ecotoxicology, 2016)

Human amniotic epithelial stem cells promote wound healing by facilitating migration and proliferation of keratinocytes via ERK, JNK and AKT signaling pathways - Bin Zhao; Jia-Qi Liu; Zhao Zheng; Jun Zhang; Shu-Yue Wang; Shi-Chao Han; Qin Zhou; Hao Guan; Chao Li; Lin-Lin Su; Da-Hai Hu (Cell and Tissue Research, 2016)

Ceramics manufacturing contributes to ambient silica air pollution and burden of lung disease - Chung-Min Liao; Bo-Chun Wu; Yi-Hsien Cheng; Shu-Han You; Yi-Jun Lin; Nan-Hung Hsieh (Environmental Science and Pollution Research, 2015)

DNA Interaction, Photocleavage and Topoisomerase I Inhibition by Ru(II) Complex with a New Ligand Possessing Phenazine Unit - Xue-Wen Liu; You-Ming Shen; Jun-Shi Shu; Yang Xiao; Song-Bai Zhang; Ji-Lin Lu (Journal of Fluorescence, 2015)

Identification of differentially expressed genes using digital gene expression profiles in Pyrus pyrifolia Nakai cv. Hosui bud release following early defoliation - Quan-jun Zhang; Shu-tian Tao; Meng Li; Xiao-xiao Qi; Jun Wu; Hao Yin; Jia-lin Deng; Shao-ling Zhang (Tree Genetics & Genomes, 2015)

Smooth muscle 22α facilitates angiotensin II-induced signaling and vascular contraction - Xiao-Li Xie; Xi Nie; Jun Wu; Fan Zhang; Li-Li Zhao; Yan-Ling Lin; Ya-Juan Yin; Hui Liu; Ya-Nan Shu; Sui-Bing Miao; Huan Li; Peng Chen; et al. (Journal of Molecular Medicine, 2015)

Regional response of dengue fever epidemics to interannual variation and related climate variability - Chung-Min Liao; Tang-Luen Huang; Yi-Jun Lin; Shu-Han You; Yi-Hsien Cheng; Nan-Hung Hsieh; Wei-Yu Chen (Stochastic Environmental Research and Risk Assessment, 2015)

Rhodococcus soli sp. nov., an actinobacterium isolated from soil using a resuscitative technique - Shan-Hui Li; Xiao-Yun Yu; Dong-Jin Park; Wael N. Hozzein; Chang-Jin Kim; Wen-Sheng Shu; Mohammed A. M. Wadaan; Lin-Xian Ding; Wen-Jun Li (Antonie van Leeuwenhoek, 2015)

Preliminary analysis of spatiotemporal pattern of global land surface water - Xin Cao; Jun Chen; LiJun Chen; AnPing Liao; FangDi Sun; Yang Li; Lei Li; ZhongHui Lin; ZhiGuo Pang; Jin Chen; ChaoYing He; Shu Peng (Science China Earth Sciences, 2014)

Effects of catechins on Agrobacterium-mediated genetic transformation of Camellia sinensis - Da-Peng Song; Lin Feng; M. M. Rana; Ming-Jun Gao; Shu Wei (Plant Cell, Tissue and Organ Culture (PCTOC), 2014)

In vitro cytotoxicity, cell cycle arrest, and antioxidation studies of ruthenium(II) complex [Ru(dmb)2(AHPIP)](ClO4)2 - De-Gang Xing; Yan Zhang; Gan-Jian Lin; Yang-Yin Xie; Shu-Yong Deng; Hong-Liang Huang; Guang-Bin Jiang; Yun-Jun Liu (Medicinal Chemistry Research, 2014)

Role of SIRT1 in Streptococcus pneumoniae-induced human β-defensin-2 and interleukin-8 expression in A549 cell - Li Lin; Shun-hang Wen; Shu-zhen Guo; Xiao-yan Su; Hu-jun Wu; Lei Chong; Hai-lin Zhang; Wei-xi Zhang; Chang-chong Li (Molecular and Cellular Biochemistry, 2014)

The study of regulatory effects of Pdx-1, MafA and NeuroD1 on the activity of porcine insulin promoter and the expression of human islet amyloid polypeptide - Xiao-Dan Liu; Jin-Xue Ruan; Ji-Han Xia; Shu-Lin Yang; Jun-Hua Fan; Kui Li (Molecular and Cellular Biochemistry, 2014)

Detection and Characterization of Avastrovirus Associated with Diarrhea Isolated from Minks in China - Na Sun; Yong Yang; Gui-Sheng Wang; Xi-Qun Shao; Shu-Qin Zhang; Feng-Xue Wang; Bin Tan; Fu-Lin Tian; Shi-Peng Cheng; Yong-Jun Wen (Food and Environmental Virology, 2014)

Gordonia jinhuaensis sp. nov., a novel actinobacterium, isolated from a VBNC (viable but non-culturable) state in pharmaceutical wastewater - Shan-Hui Li; Yi Jin; Juan Cheng; Dong-Jin Park; Chang-Jin Kim; Wael N. Hozzein; Mohammed A. M. Wadaan; Wen-Sheng Shu; Lin-Xian Ding; Wen-Jun Li (Antonie van Leeuwenhoek, 2014)

The effects of dietary thiamin on oxidative damage and antioxidant defence of juvenile fish - Xue-Yin Li; Hui-Hua Huang; Kai Hu; Yang Liu; Wei-Dan Jiang; Jun Jiang; Shu-Hong Li; Lin Feng; Xiao-Qiu Zhou (Fish Physiology and Biochemistry, 2014)

Effect of dietary lysine on growth, intestinal enzymes activities and antioxidant status of sub-adult grass carp (Ctenopharyngodon idella) - Xue-Yin Li; Ling Tang; Kai Hu; Yang Liu; Wei-Dan Jiang; Jun Jiang; Pei Wu; Gang-Fu Chen; Shu-Hong Li; Sheng-Yao Kuang; Lin Feng; Xiao-Qiu Zhou (Fish Physiology and Biochemistry, 2014)

Identification of the substrate recognition region in the Δ6-fatty acid and Δ8-sphingolipid desaturase by fusion mutagenesis - Li-Ying Song; Yan Zhang; Shu-Fen Li; Jun Hu; Wei-Bo Yin; Yu-Hong Chen; Shan-Ting Hao; Bai-Lin Wang; Richard R.-C. Wang; Zan-Min Hu (Planta, 2014)

Antioxidant status of serum, muscle, intestine and hepatopancreas for fish fed graded levels of biotin - Lin Feng; Shu Zhao; Gangfu Chen; Weidan Jiang; Yang Liu; Jun Jiang; Kai Hu; Shuhong Li; Xiaoqiu Zhou (Fish Physiology and Biochemistry, 2014)

Efficacy of Various Combined Blood Purification Techniques for Treating Patients with Non-viral Acute Liver Failure - Mao-qin Li; Jia-qiong Li; Zai-xiang Shi; Ji-yuan Xu; Zhou Zhang; Fei Lu; Lin Li; Yan-jun Xu; Xun Mo; Bo Lu; Xiao-meng Wang; Li-li Ma; et al. (Cell Biochemistry and Biophysics, 2014)

Hierarchically Clustering to 1,033 Genes Differentially Expressed in Mouse Superior Colliculus in the Courses of Optic Nerve Development and Injury - Qiang Mei; Yan-qi Zhang; Jian-jun Liu; Cheng-ren Li; Xing-shu Chen; Hong-li Li; Mao-lin Qin; Ya-zhou wu; Yun-lai Liu; Wen-qin Cai (Cell Biochemistry and Biophysics, 2013)

Suggestion of GLYAT gene underlying variation of bone size and body lean mass as revealed by a bivariate genome-wide association study - Yan-Fang Guo; Li-Shu Zhang; Yong-Jun Liu; Hong-Gang Hu; Jian Li; Qing Tian; Ping Yu; Feng Zhang; Tie-Lin Yang; Yan Guo; Xiang-Lei Peng; Meng Dai; et al. (Human Genetics, 2013)

Comparative study of four rice cultivars with different levels of cadmium tolerance - Xiao Wang; Zhong-Wei Zhang; Shi-Hua Tu; Wen-Qiang Feng; Fei Xu; Feng Zhu; Da-Wei Zhang; Jun-Bo Du; Shu Yuan; Hong-Hui Lin (Biologia, 2013)

Tenuibacillus halotolerans sp. nov., a novel bacterium isolated from a soil sample from a salt lake in Xinjiang, China and emended description of the genus Tenuibacillus - Xu-Hong Gao; Sheng Gao; Yu Zhou; Hui-Lin Guan; Yun-Jiao Zhang; Man Jia; Hua-Wei Huang; Dong-Xu Yang; Wen-Jun Li; Shu-Kun Tang (Antonie van Leeuwenhoek, 2013)

Time-dependent expression and distribution of Egr-1 during skeletal muscle wound healing in rats - Yan-Yan Fan; Guang-Hua Ye; Ke-Zhi Lin; Lin-Sheng Yu; Shu-Zhen Wu; Miao-Wu Dong; Jun-Ge Han; Xiang-Ping Feng; Xing-Biao Li (Journal of Molecular Histology, 2012)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

VEGF is essential for the growth and migration of human hepatocellular carcinoma cells - Lei Zhang; Jia-Ning Wang; Jun-Ming Tang; Xia Kong; Jian-Ye Yang; Fei Zheng; Ling-Yun Guo; Yong-Zhang Huang; Li Zhang; Lin Tian; Shu-Fen Cao; Chang-Hai Tuo; et al. (Molecular Biology Reports, 2012)

Genome-wide association study identifies HMGN3 locus for spine bone size variation in Chinese - Shu-Feng Lei; Hui Shen; Tie-Lin Yang; Yan Guo; Shan-Shan Dong; Xiang-Hong Xu; Fei-Yan Deng; Qing Tian; Yong-Jun Liu; Yao-Zhong Liu; Jian Li; Hong-Wen Deng (Human Genetics, 2012)

Molecular genetic studies of gene identification for sarcopenia - Li-Jun Tan; Shan-Lin Liu; Shu-Feng Lei; Christopher J. Papasian; Hong-Wen Deng (Human Genetics, 2012)

Olig1 and ID4 interactions in living cells visualized by bimolecular fluorescence complementation technique - Shu-Jun Guo; Jian-Guo Hu; Bao-Ming Zhao; Lin Shen; Rui Wang; Jian-Sheng Zhou; He-Zuo Lü (Molecular Biology Reports, 2011)

New cytotoxic oxygenated sterols from marine bryozoan Bugula neritina - Fan Yang; Hong-Jun Zhang; Jian-Tao Chen; Hai-Feng Tang; Shu-Juan Piao; Wan-Sheng Chen; Hou-Wen Lin (Natural Product Research, 2011)

Ningdong granule: a complementary and alternative therapy in the treatment of attention deficit/hyperactivity disorder - Ji-Jun Li; Zai-Wang Li; Shu-Zhen Wang; Fang-Hua Qi; Lin Zhao; Hong Lv; An-Yuan Li (Psychopharmacology, 2011)

Role of microRNA-21 and effect on PTEN in Kazakh’s esophageal squamous cell carcinoma - Wen-jing Ma; Guo-dong Lv; Aerziguli Tuersun; Qing Liu; Hui Liu; Shu-tao Zheng; Cong-gai Huang; Jun-guo Feng; Xing Wang; Ren-yong Lin; Ilyar Sheyhidin; Xiao-mei Lu (Molecular Biology Reports, 2011)

Comparative expression analysis of dehydrins between two barley varieties, wild barley and Tibetan hulless barley associated with different stress resistance - Jun-Bo Du; Shu Yuan; Yang-Er Chen; Xin Sun; Zhong-Wei Zhang; Fei Xu; Ming Yuan; Jing Shang; Hong-Hui Lin (Acta Physiologiae Plantarum, 2011)

Characterization of a male sterile mutant from progeny of a transgenic plant containing a leaf senescence-inhibition gene in wheat - Ya-Jun Xi; Xue-Feng Ma; Huan Zhong; Shu-Dong Liu; Zhu-Lin Wang; Yang-Yang Song; Cheng-Hui Zhao (Euphytica, 2011)

Th17 promotes acute rejection following liver transplantation in rats - Xiao-jun Xie; Yu-fu Ye; Lin Zhou; Hai-yang Xie; Guo-ping Jiang; Xiao-wen Feng; Yong He; Qin-fen Xie; Shu-sen Zheng (Journal of Zhejiang University-SCIENCE B, 2010)

Development of two new molecular markers specific to cytoplasmic male sterility in tuber mustard (Brassica juncea var. tumida Tsen et Lee) - Xiao-lin Yu; Qiu-bin Xiao; Jia-shu Cao; Zhu-jun Chen; Yutaka Hirata (Euphytica, 2009)

Genome-wide association scan for stature in Chinese: evidence for ethnic specific loci - Shu-Feng Lei; Tie-Lin Yang; Li-Jun Tan; Xiang-Ding Chen; Yan Guo; Yan-Fang Guo; Liang Zhang; Xiao-Gang Liu; Han Yan; Feng Pan; Zhi-Xin Zhang; Yu-Mei Peng; et al. (Human Genetics, 2009)

Role of P-glycoprotein in Limiting the Brain Penetration of Glabridin, An Active Isoflavan from the Root of Glycyrrhiza glabra - Xi-Yong Yu; Shu-Guang Lin; Zhi-Wei Zhou; Xiao Chen; Jun Liang; Xue-Qing Yu; Balram Chowbay; Jing-Yuan Wen; Wei Duan; Eli Chan; Xiao-Tian Li; Jie Cao; et al. (Pharmaceutical Research, 2007)

Streptomyces serianimatus sp. nov., isolated from a rhizophere soil - Yong-Xia Wang; Xiao-Yang Zhi; Hua-Hong Chen; Yu-Qin Zhang; Shu Kun Tang; Cheng-Lin Jiang; Li-Hua Xu; Wen-Jun Li (Antonie van Leeuwenhoek, 2007)

Identification and fine mapping of AvrPi15, a novel avirulence gene of Magnaporthe grisea - Jun-Hong Ma; Ling Wang; Shu-Jie Feng; Fei Lin; Yi Xiao; Qing-Hua Pan (Theoretical and Applied Genetics, 2006)

Streptomyces daliensis sp. nov. from soil - Ping Xu; Wen-Jun Li; Shu-Kun Tang; Hui-Ying Gao; Li-Hua Xu; Cheng-Lin Jiang (Antonie van Leeuwenhoek, 2006)

Status of Biological Studies and Aquaculture Development of the Mud Crab, Scylla serrata, in China: An Experimental Ecological Studies - Wang Gui-zhong; Li Shao-jing; Zeng Chao-shu; Lin Shu-jun; Kong Xiang-hui; Ai Chun-xiang; Lin Qiong-wu (Aquaculture International, 2005)

Edge detection method of remote sensing images based on mathematical morphology of multi-structure elements - Hui Lin; Pei-jun Du; Chang-sheng Zhao; Ning Shu (Chinese Geographical Science, 2004)

Spatial and temporal dynamics of soil organic carbon in reserved desertification area - Shu-lan Cheng; Hua Ouyang; Hai-shan Niu; Lin Wang; Feng Zhang; Jun-qin Gao; Yu-qiang Tian (Chinese Geographical Science, 2004)

Release Kinetics of Water Soluble Organic Carbon (WSOC) from River Sediment and Wetland Soil - Shu Tao; Bin Lin; Xiaohang Liu; Jun Cao (Water, Air, & Soil Pollution, 2000)